ANALISIS TINGKAT PERCERAIAN DI RIAU: PERAN KONSELING PERNIKAHAN DALAM MENCEGAH DAN MENGATASI PERMASALAHAN RUMAH TANGGA - Reizki Maharani; Firman; Afdal (Yayasan Amanah Nur Aman, 2025)
The divorce rate in Indonesia, especially in the Riau region, has shown a quite significant increase in recent years. This phenomenon has become a very important issue to be considered in social and psychological studies, especially considering the broad and profound impact it has on individuals, families, and society as a whole. This article aims to conduct an in-depth analysis of the factors that contribute to the increasing divorce rates in Riau, as well as evaluate the role of marriage counseling in efforts to prevent and resolve various issues that arise in marital life. In conducting this analysis, the article adopts a literature study approach, where data and information are gathered from various relevant sources to provide a more comprehensive and thorough overview of the divorce issue currently happening in Riau society. With this approach, it is hoped that readers can better understand the complexity of divorce problems and the solutions that can be implemented to reduce divorce rates in the region.